(untitled) (Sciences & Technologie. C, Biotechnologies, 2002)
Seasonal dynamics and life history traits of one population of the cladoceran Daphnia chevreuxi Richard were monitored under field and laboratory conditions. Temperature dependent demographic traits (birth, size, longevity and development rates) were followed throughout the year. The influence of predation, through the use of fish kairomones, on life history traits has been investigated and the main response to fish chemicals has been shown to be a decrease in size at first reproduction (S.F.R.).